REHABILITASI MEDIK PADA ANAK DENGAN LEUKEMIA LIMFOBLASTIK AKUT - Yenni, . (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Acute lymphoblastic leukemia (ALL) is oftenly found in children as well as in adolescents. ALL occurs in 3-4 cases of 100,000 children. The specific etiology of ALL is still unknown, but it is related to a multifactorial process associated with genetic, immunology, environment, toxic substances, viral exposures, and ionization radiation. Clinical manifestations of ALL may include fatigue and weakness, palor, infections and febris that are not improved with antibiotics, easy bleeding or bruising, joint or bone pain, loss of appetite, weight loss, enlarged lymph nodes, cough, or difficulty of breathing, enlargement of the liver or spleen, swelling of the face and hands, headaches, and vomiting. Functional improvement is a goal for medical rehabilitation in patient with LLA. In general, cancer rehabilitation management aims to maintain body functions including mobilization and activity, nutrition, social support systems, and pain control. Moreover, the program is implemented in conjunction with specific interventions based on the affected organ systems.Keywords: ALL, medical rehabilitationAbstrak: Leukemia limfoblastik akut (LLA) merupakan kanker yang sering terjadi pada anak-anak dan remaja. LLA terjadi pada 3-4 kasus dari 100.000 anak. Etiologi spesifik LLA belum diketahui, tetapi berhubungan dengan proses multifaktorial yang berkaitan dengan genetik, imunologi, lingkungan, toksik, paparan virus, ionization radiation. Manifestasi klinik leukemia dapat berupa kelelahan dan kelemahan, kulit pucat, infeksi dan demam yang tidak sembuh dengan antibiotik, mudah berdarah atau memar, nyeri sendi atau tulang, hilangnya nafsu makan dan turunnya berat badan, pembesaran kelenjar limfe, batuk atau kesulitan pernafasan, pembesaran hati atau limpa, pembengkakan muka dan tangan, sakit kepala, dan muntah Perbaikan status fungsional merupakan tujuan utama rehabilitasi medik pasien LLA. Penanganan rehabilitasi kanker secara umum ialah untuk memelihara fungsi meliputi mobilisasi, aktivitas, nutrisi, sistem pendukung sosial dan pengendalian rasa nyeri. Keseluruhan program ini diterapkan bersamaan dengan intervensi spesifik berdasarkan sistem organ yang terkena.Kata kunci: LLA, rehabilitasi medik